2021
DOI: 10.1186/s40813-021-00241-y
|View full text |Cite
|
Sign up to set email alerts
|

Fermented rye with Agaricus subrufescens and mannan-rich hydrolysate based feed additive to modulate post-weaning piglet immune response

Abstract: Background The process of weaning in piglets is often associated with an increased inflammation response in the intestine and compromised intestinal integrity and morphology, favoring a delay in intestinal maturation and a predisposal to diseases. Research has shown the potential of different nutritional strategies to reduce the production of pro-inflammatory cytokines, with the main goal to manipulate health and performance of pigs. Promising examples of nutritional strategies are fungal ferme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 82 publications
2
3
0
Order By: Relevance
“…This is strengthened by our observation that genes involved in the Dectin-1/TLR signalling pathway (e.g., IRAK1, IRAK4, Myd88, NFKBIA, NFKB2, and TOLLIP) were significantly different between the treatment groups. In line with our findings, de Groot et al demonstrated that ROM combined with mannan-rich hydrolysed copra meal increased the number of NK cells in porcine blood on day 15 post-weaning [ 11 ]. Another study that used gene-targeted mice and neutralizing monoclonal antibodies clearly showed that A. subrufescens augmented NK cell cytotoxicity through IL-12-mediated IFN-γ production [ 97 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is strengthened by our observation that genes involved in the Dectin-1/TLR signalling pathway (e.g., IRAK1, IRAK4, Myd88, NFKBIA, NFKB2, and TOLLIP) were significantly different between the treatment groups. In line with our findings, de Groot et al demonstrated that ROM combined with mannan-rich hydrolysed copra meal increased the number of NK cells in porcine blood on day 15 post-weaning [ 11 ]. Another study that used gene-targeted mice and neutralizing monoclonal antibodies clearly showed that A. subrufescens augmented NK cell cytotoxicity through IL-12-mediated IFN-γ production [ 97 ].…”
Section: Discussionsupporting
confidence: 92%
“…Fabà et al reported that feeding ROM combined with organic acids to nursery pigs reduced S. Typh shedding over a 21-day period post-challenge [ 10 ]. De Groot et al observed that inclusion of a blend of ROM combined with mannan-rich hydrolysed copra meal for nursery pigs exerted immunomodulatory effects both in the GI tract and at systemic level [ 11 ]. Recently, the neonatal period (spanning birth to weaning) has been described as a critical “window of opportunity” that allows for an important cross-talk between gut microbiota and immune system [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is strengthened by our observation that genes involved in the Dectin-1/TLR signalling pathway (e.g., IRAK1, IRAK4, Myd88, NFKBIA, NFKB2, and TOLLIP) were signi cantly different between the treatment groups. In line with our ndings, de Groot et al demonstrated that ROM combined with mannan-rich hydrolysed copra meal increased the number of NK cells in porcine blood on day 15 post-weaning [11]. Another study that used gene-targeted mice and neutralizing monoclonal antibodies clearly showed that A. subrufescens augmented NK cell cytotoxicity through IL-12-mediated IFN-γ production [96].…”
Section: Discussionsupporting
confidence: 83%
“…Fabà et al reported that feeding ROM combined with organic acids to nursery pigs reduced S. Typh shedding over a 21-day period post-challenge [10]. De Groot et al observed that inclusion of a blend of ROM combined with mannan-rich hydrolysed copra meal for nursery pigs exerted immunomodulatory effects both in the GI tract and at systemic level [11]. Recently, the neonatal period (spanning birth to weaning) has been described as a critical "window of opportunity" that allows for an important cross-talk between gut microbiota and immune system [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study [ 69 ] showed the potential immunomodulatory effect of compound F when supplementing piglets post-weaning, with a reduction of pro-inflammatory cytokine production in jejunum, ileum, and colon. In our study, no significant differences in cytokine mRNA levels were observed after L. intracellularis challenge ( Figure 2 B).…”
Section: Discussionmentioning
confidence: 99%